ANALISIS KINERJA PEGAWAI DI KANTOR RADIO VOLARE KOTA PONTIANAK - Mutining Mutining (STIE 'INDONESIA' Pontianak, 2017)
ThisstudyaimstofindpracticalandanalyzeperformanceofemployeesofRadioVolare Pontianak, in order to match an employees’ performance improvement strategy. While theoretically the results of this study are expected to provide an overview performance of employees of Radio Volare Pontianak . The results with observations of phenomena such as the above shows that the performance of employees of Radio Volare Pontianak has not been optimal.It is with the persistence of the level of discipline, motivation and responsibility are still lacking on the field. But with the education and training, coaching, development of potential employees, giving reward and punishment as well as good relations between leaders and employees will contribute both to improve employee performance on an goingbasis.